Dehydrocurvularin is a potent antineoplastic agent irreversibly blocking ATP-citrate lyase: evidence from chemoproteomics - Deng, Zhangshuang; Wong, Nai-Kei; Guo, Zhiyong; Zou, Kun; Xiao, Youli; Zhou, Yiqing (Chemical communications (Cambridge, England), 2019)
Natural-product macrolide 10,11-dehydrocurvularin ( DCV ) was revealed to be a potent irreversible inhibitor of ATP-citrate lyase (ACLY) via classical chemoproteomic profiling, which mechanistically illuminates the anti-cancer mode of action of DCV and its analogues. Dehydrocurvularin irreversibly inhibits human ATP-citrate lyase.